New Insights on the Early Interaction Between Typhoid and Non-typhoid Salmonella Serovars and the Host Cells - Schultz, Bárbara M.; Melo-Gonzalez, Felipe; Salazar, Geraldyne A.; Porto, Bárbara N.; Riedel, Claudia A.; Kalergis, Alexis M.; Bueno, Susan M. (Frontiers in Microbiology, 2021)
Salmonella enterica is a common source of food and water-borne infections, causing a wide range of clinical ailments in both human and animal hosts. Immunity to Salmonella involves an interplay between different immune responses, which are rapidly initiated to control bacterial burden. However, Salmonella has developed several strategies to evade and modulate the host immune responses. In this sense, the main knowledge about the pathogenicity of this bacterium has been obtained by the study of mouse models with non-typhoidal serovars. However, this knowledge is not representative of all the pathologies caused by non-typhoidal serovars in the human. Here we review the most important features of typhoidal and non-typhoidal serovars and the diseases they cause in the human host, describing the virulence mechanisms used by these pathogens that have been identified in different models of infection.